Process evaluation of Internet-based cognitive behavioural therapy for adults with tinnitus in the context of a randomised control trial - Beukes, Eldre W.; Manchaiah, Vinaya; Baguley, David M.; Allen, Peter M.; Andersson, Gerhard (Taylor & Francis, 2017)
Objective: The research objective was to identify processes that could either facilitate or hinder clinical implementation of an Internet-based cognitive behavioural therapy intervention for tinnitus in the UK. This was done by exploring the research context, the intervention components and the factors that contributed to the outcomes obtained. Design: This study investigated eight processes including the recruitment strategies, reach, research context, treatment dose delivered and received, implementation fidelity, barriers to implementation and effectiveness of the intervention. Study sample: Of the 169 registered participants, 146 were randomly assigned to the experimental or control groups (23 were excluded). The mean age was 55.57 years with an average tinnitus duration of 11.63 years. Results: The intended sample of people with distressing tinnitus who were underserved with evidence-based tinnitus interventions was reached. The full guided intervention was delivered. The recommended modules were read more than the optional modules. Intervention components such as the easily readable format and the benefits of the applied relaxation programme facilitated significant positive post-intervention outcomes. Barriers hampering the intervention application included time pressures and low self-motivation. Conclusions: Results of this process evaluation together with the outcome data can be used to facilitate translating this research into clinical practice.